Blockchain Applications in the Agri-Food Domain: The First Wave - Motta, Giorgio Alessandro; Tekinerdogan, Bedir; Athanasiadis, Ioannis N. (Frontiers in Blockchain, 2020)
This study aims to investigate the application potential of blockchain technology in the agri-food industry, by following a case study approach focused on the early adopter companies. As the topic is emerging, there are not enough academic papers available to warrant a systematic literature review. To confirm this hypothesis and to inform to better understand guide this research, we first conducted a pre-literature review. Based on its outcomes, we formulated three research questions, and developed a protocol to identify case studies, and subsequently analyzed them to answer our questions. We identified and studied six case studies, in which blockchain has been used to address issues of trust and transparency, and to facilitate information sharing among agrifood chain stakeholders. While blockchain adoption is still in its infancy, governance issues are important, as broader partnerships are required for successful, sustainable applications.